Afterword: the Scottish referendum, the English question and the changing constitutional geography of the United Kingdom. Issue 1 (12th January 2015) - Clifford, Ben; Morphet, Janice
<x xml:space="preserve">Abstract</x> The referendum held in Scotland on 18 September 2014 resulted in a rejection of the option of becoming an independent nation‐state. The perceived closeness of the vote, however, led to a rush of promises for further devolution from UK politicians. This crisis seems to have resulted in a period of constitutional flux throughout the United Kingdom, with demands for further powers for Northern Ireland and Wales, as well as a broad debate on the status of England. There have also been recent pronouncements on further city‐regional devolution within England. The changing political geography of the United Kingdom can be understood in a European context and as part of longstanding debate about the rescaling of the state. Briefly considering the key issues of sovereignty and territorial identity, we argue that nation‐states will continue to play an important role in our governance for the foreseeable future, but that there needs to be further devolution in the United Kingdom. Any changes to our state spatial structures will proceed in a halting and path‐dependent manner.